HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN PERILAKU PEMERIKSAAN IVA SEBAGAI SKRINING KANKER SERVIKS PADA WANITA USIA SUBUR DI UPTD PUSKESMAS KUTA UTARA - Ni Putu Atrinitati; Putu Mastiningsih; Pande Novi Ekajayanti; Ni Made Risna Sumawati (Jurnal Maternitas Kebidanan, 2024)
Cervical cancer is cancer that attacks the cervix and is the second highest cause of death in women and is the main cause of death for women in developing countries. One of the diseases that is a health problem that is feared to occur in women throughout the world is cervical cancer. One early detection that can be done is an IVA examination. The low coverage of IVA examinations in women of childbearing age can be influenced by several causal factors such as the level of knowledge and support from husbands. Husband's support is a significant factor in influencing the reproductive age of women in Indonesia to carry out VIA examinations. This research aims to determine the correlation between the level of husband's knowledge and support and the behavior of VIA examinations as cervical cancer screening in women of childbearing age at the UPTD of the North Kuta Health Center. This research utilized a quantitative approach. The research design used in this research is a cross-sectional research design, namely an observational (non-experimental) study which includes all types of research in which variables are measured only once, at one time. The sample in this study was reproductive-age women amounting to 82 people. Sampling technique using Purposive Sampling Technique. Data were analyzed using analysis using the chi-square test α <0.05. According to the research above, the results acquired utilizing statistical tests in this study were carried out using the chi-square test, the statistical showed a p-value of 0.010. These findings showed that H0 is rejected and Ha is accepted, which means there is a significant correlation between the husband's support and the behavior of IVA examinations as cervical cancer screening in women of childbearing age at the UPTD Puskesmas Utara Kuta. Based on the findings of this study, it is hoped that women of childbearing age can carry out IVA examinations as cervical cancer screening at UPTD North Kuta Health Center.